Effect of pH on visible-light-driven Bi2WO6nanostructured catalyst synthesized by hydrothermal method - Anukorn Phuruangrat (2018)
© 2014 Elsevier Ltd. All rights reserved. In this research, effect of pH on phase, morphologies and photocatalytic activities of Bi 2 WO 6 synthesized in the precursor solution with the pH of 2-12 by the 180 °C and 20 h hydrothermal reaction is reported. The as-synthesized Bi 2 WO 6 products were characterized by X-ray powder diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FTIR) spectrophotometry, Brunauer-Emmett-Teller (BET) isotherm, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and UV-visible spectroscopy. The photocatalytic activities of the as-synthesized Bi 2 WO 6 products were evaluated via the photodegradation of rhodamine B (RhB) under visible-light radiation. The results showed that the precursor solution pH had an important influence on the photocatalytic activities of the Bi 2 WO 6 nanocatalyst. When the precursor solution pH was 2, the RhB degradation exhibited the highest decolorization efficiency of 98% within 100 min.